Studi Hubungan Karakteristik Tipologi Lahan yang Digunakan terhadap Kualitas Hasil Jeruk Siem (Citrus nobilis var. microcarpa) di Kabupaten Sambas - Agus Suyanto; Tutik Purwani Irianti (Perkebunan dan Lahan Tropika, 2011)
The purpose of this research was to know the characteristic relationship of the land typology that has been used towards the quality of jeruk siem (Citrus nobilis var. microcarpa) at Sambas Regency. This research was performed in Sambas Regency at each of the jeruks society farm management and also from the private sector. This research was done by field survey and direct observation towards soil sample and plant based on the characteristic and cultivation system of jeruk siam. The location of soil sample and plant was the field sample in the Tebas Kuala, Tebas Sungai, Mekar Sekuntum, Segedong, Sempalai, dan Seberkat. The sample was divided into three sample based on the cultivation system and the land typology that were consists of land typology 1 with the farmer technology package, land typology 2 with the advised technology package and land typology 3 with advised technology. The characteristic of the land typology was connected to the yield of the quality of the jeruk siem. The good land characteristic, whereas the macro nutrient content and micro that available for the plant and having the good land texture, so that the nutrient that contented in the soil cannot be so easily loss by the development of the fruit that propped by the content of the equivalent and adequately nutrient availability by the fertilizer. From the result of the research the best land was the land typology 2 with the advised technology in Mekar Sekuntum Kec. Tebas, that can be seen from the whole of the observe variable in the research with the fruit diameter was 5.85 mm, the weight of fruit was 133,33 g, the weight of juice was 60.63 g, the thick epidermis was 0.23 mm, the weight of epidermis was 21.26 g, water condense of the fruit was 46.88% and the vitamin C was 50,40 mg.